Analysis of tire contact stresses and asphalt pavement rutting under gradient temperature and typical driving conditions - Minrui Guo; Pei Liu; Wei Feng; Xiangwen Li; Haitao Ge (Scientific Reports)
Abstract Studies on triaxial contact stresses and asphalt pavement rutting are of great significance for traffic safety and the durability of the asphalt pavement. Our new approach considers more evaluating indicators by investigating compressive creep, vertical, and longitudinal permanent deformation to analyse asphalt pavement rutting under triaxial contact stress during typical driving conditions. For this purpose, firstly sophisticated three-dimensional finite element models encompassing the truck-bus tire and asphalt pavement temperature are developed. Secondly, a comparative analysis was conducted by collating the predicted deformations obtained through finite element analysis with the deformations measured in laboratory experiments using specialized sensors. Finally, the rutting analysis process under triaxial contact stresses during typical driving conditions is established. The results show asphalt pavement exhibits different temperature gradient changes between daytime and nighttime during the summer season. The longitudinal contact stress under braking condition has a significant impact on the longitudinal permanent deformation and compressive creep of asphalt pavement, especially, the longitudinal permanent deformation of the feature points in the middle layer exhibits the most pronounced sensitivity to this contact stress. In addition, the maximal compressive creep is observed at the top of the middle layer, although the characteristic positions for the maximum values of positive and negative creep differ. The proposed new method is beneficial for improving the accuracy and comprehensiveness of asphalt pavement rutting analysis.